Synthesis, characterization and biological properties of palm catanionic surfactants / Wong Siew Pui - Wong, Siew Pui (2014)
Surfactant is well known for its versatility in many forms of applications. Today, new types of surfactants continue to emerge and evolve to cater to the changing needs of industries. One of these interesting and promising new surfactants is catanionic surfactant. Its unique aggregation behaviour and superior surface activities have sparked interests to many researchers in the area of colloidal chemistry. In our study, CmMES.CnTAB catanionic surfactants were formed by mixing equimolar ratio of cationic surfactant alkyltrimethylammonium bromide (CnTAB) and anionic surfactant sodium methyl ester α-sulfonate (CmMES). Precipitation method coupled with cold filtration system was employed to obtain the white precipitate of CmMES.CnTAB catanionic surfactants. All samples were characterized by fourier transform infrared and NMR spectroscopies. Spontaneous formation of vesicles of CmMES.CnTAB catanionic surfactants was also observed under optical polarizing microscope. The surface properties of binary mixtures of anionic sodium methyl ester α-sulfo alkylate (CmMES) and cationic alkyltrimethylammonium bromide (CnTAB) of different carbon chain length were studied using tensiometer via du Nuoy ring method. The critical micelle concentration (CMC) obtained from the plots of surface tension (γ) versus concentration showed that mixed surfactants have CMC values of about 10 times lower than their single components. The large negative values for both interaction parameters suggest the existence of strong synergism between the oppositely charged surfactant molecules. The average interaction parameter values are approximately -14. Effect of hydrocarbon chain length of either surfactant was also compared and the results showed that the effect of cationic surfactant chain length dominated that of the anionic surfactants. It was also discovered that certain mixed surfactant combinations behave differently from the expected trend. Aggregation behaviour of CmMES.CnTAB catanionic surfactants at the air/water interface were explained by surface tension measurement technique. Surface activities of catanionic surfactants were extremely high with critical micelle concentration (CMC) values from as low as 0.01 mM. This is further confirmed by the surface excess concentration, Гmax and minimum area, Amin values of the catanionic surfactants. Besides that, catanionic surfactants with lower alkyl chain length were found to have greater ability in decreasing the air/water interfacial tension. Anionic/cationic mixtures and catanionic surfactants were also bioassayed on both Gram-positive (Staphylococcus aureus, SA) and Gram-negative (Escherichia coli, EC and Pseudomonas aeruginosa, PA) using broth dilution method. Both anionic/cationic mixed surfactants and catanionic surfactant solutions showed excellent in-vitro antibacterial activity against SA ranging from 1.25 to 125 μM and had variable activity against EC with minimum inhibitory concentration (MIC) of 10 to 1250 μM but were less active against PA. Inhibitive power of anionic/cationic mixtures was on par with single CnTAB surfactants; with certain mixtures even have lower minimum inhibition concentration (MIC) than single CnTAB surfactants. Besides that, anionic/cationic mixed surfactants at equimolar mixing ratio showed exceptional inhibitive power against SA and EC. Although catanionic surfactants have higher surface activities, but they were less potent towards all three microbes as compared to its anionic/cationic mixtures.